Group technology in systems integration - Raneses, Nestor O. (Philippine Engineering Journal)
Systems integration (SI) requires that components must be thoroughly analyzed, simplified, standardized and optimized over its lifespan to achieve true integration. Group technology (GT) provides a rational framework for integrating systems. GT is a disciplined approach of grouping parts, process, equipment, tools, people, information, energy or subsystems based on similarities and optimizing their efficiency and effectiveness over time. It involves attribute identification and family formation, classification and coding, simplification, standardization and optimization. Family formation, classification and coding are the cornerstones of group technology. We have established that GT is a science-based concept which has many potential applications for simplifying, standardizing and optimizing complex systems. Design guidelines on how to effectively carry out GT are given. Specific research and development trajectories are suggested.